ANALISIS KINERJA ORGANISASI KELURAHAN WONOKROMO DALAM PELAYANAN PUBLIK KOTA SURABAYA - Agustina, Nimas Wahyu; Raharja, Wildan Taufik (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
Service is an effort to to provide a product to customers, one of which is a public organization such as the Wonokromo Village office which provides products in the form of public services by trying to provide good performance so that people feel happy and satisfied. The purpose of this writing is to find out what are the supporting and inhibiting factors in addition to analyzing and knowing how the performance has been carried out by the Wonokromo Village office. The method used in this writing uses qualitative research methods with organizational performance analysis from Agus Dwiyanto. The results obtained from field research are that Wonokromo Village has good performance and is also productive, besides that the services and explanations provided are very helpful to local residents but this does not escape the existence of supporting factors that support good performance, one of which is the existence of performance training conducted but there are inhibiting factors that are felt to be resolved immediately in the form of building infrastructure and lack of facilities in the office.